Efficacy And Safety Of Sofosbuvir/ Daclatasvir VS Sofosbuvir/Velpatasvir In Chronic Hepatitis C Patients (Medical Forum Monthly, 2024)
Objective: The present study aims to compare the efficacy and safety of SOF/DCV and SOF/VEL in treating chronic hepatitis C patients.Study Design: Randomized controlled trial study.Place and Duration of Study: This study was conducted at the SKBZ hospital CMH Muzaffarabad from 1st July 2023 to 30th June 2024.Methods: Through non probability consecutive sampling, 200 patients aged above 18 years, either gender, diagnosed with Chronic HCV (Viral titer >10, 000 IU/mL) were included in the present study. Co-infection with hepatitis B virus (HBV) or human immunodeficiency virus (HIV), decompensated liver disease, significant renal impairment, pregnant patients were excluded from the present study. Patients were randomized in a 1:1 ratio to receive either SOF/DCV (400 mg Sofosbuvir and 60 mg Daclatasvir daily) (n=100) or SOF/VEL (400 mg Sofosbuvir and 100 mg Velpatasvir daily) (n=100), with treatment extending for 12 weeksResults: The baseline HCV viral titer in the patients of both study groups were 6.84±0.5 and 7.1±0.9 g/dL (p<0.0001). Sustained virological response (SVR) at 12- week was achieved in 92% patients in SOF/DCV group and 95% in SOF/VEL group. Mild adverse effects were observed in both the study groupsConclusion: In conclusion, the efficacy in achieving sustained viral response (SVR) in the group managed by Sofosbuvir and velpatasvir was higher (95%) against Sofosbuvir and Daclatasvir (92%).